Effect of ultrasonication on alkaline treatment of empty fruit bunch fibre : Fourier Transform Infrared Spectroscopy (FTIR) and morphology study - Wan Mohd Eqhwan, Iskandar; Ong, Huei Ruey; Khan, Md Maksudur Rahman; Ridzuan, Ramli (Elsevier Ltd, 2022)
This study highlights the usage of ultrasonication method in NaOH surface modification of empty fruit bunch (EFB) fibre. Fibres were characterized by Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The EFB treated by ultrasonication assisted alkali treatment shows better morphology with smoothed surface and less impurities. Furthermore, it was found that disappear of peak between 2900 and 1700 cm-1 (C[sbnd]H) evidenced the removal of hemicellulose on EFB fibre surface by alkali treatment. Moreover, Ultrasonication assisted alkali method illustrate the excellent value in enhancing the tensile stress of EFB fibre compared to other technique. The results suggest that ultrasonication assisted alkali treatment have the potential to be used in industry as the surface modification method.